STUDENTS’ PERSPECTIVES ON A SCHOOL-BASED ENGLISH PROGRAM - Francine Soimeng Pang; Meihua Liu (Indonesian JELT, 2006)
This article reports a study on students’ perspectives on a summer school program, a school-based Café aimed at learning spoken English. Administering a 15-item survey to 1,331 students at six different grade levels at a Macao secondary school, the study revealed that (1) most of the students were not motivated to learn spoken English, (2) the majority of the students held negative attitudes towards the school-based English program, (3) the students at higher grade levels tended to be significantly more motivated and held more positive attitudes towards the program, (4) male students were significantly more motivated and thought more highly of the program than their female counterparts, and (5) the students’ English-learning motivation and attitudes towards the program were significantly positively correlated with their English proficiency. Finally, some suggestions and implications were discussed. Keywords:  students’ perspectives, motivation, attitude, spoken English, grade level